Effect of five-element music therapy combined with auricular acupoint pressing on emotional status and sleep quality of patients with peritoneal dialysis (五行音乐联合耳穴贴压对腹膜透析患者情志与睡眠质量的影响研究) - ZHOU Gexia (周革霞); LI Qian (李倩); LI Yanshuang (李艳爽); ZHAO Yan (赵妍); ZHANG Caijuan (张彩娟); JIANG Shan (姜珊); SHAO Jinghua (邵京华) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of five-element music therapy combined with auricular acupoint pressing on emotional status and sleep quality of patients with peritoneal dialysis. Methods Totally 80 peritoneal dialysis patients with catheter placement were randomly divided into the control group and the intervention group, with 40 cases in each group. All patients received routine care and emotion nursing, and those in the intervention group were given five-element music therapy combined with auricular acupoint pressing. The anxiety, depression status and sleep quality of patients were evaluated. Results The scores of Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) decreased in both groups after a two-week intervention, and were lower in the intervention group than those in the control group (P<0. 01). The score of Pittsburgh Sleep Quality Index (PSQI) decreased in both groups after a two-week intervention, and was lower in the intervention group than that in the control group (P<0. 01). Conclusion On the basis of routine care and emotion nursing, the five-element music therapy combined with auricular acupoint pressing is effective to improve the emotional status and sleep quality of patients with peritoneal dialysis. (目的 探讨五行音乐联合耳穴贴压对腹膜透析患者情志与睡眠质量的影响。方法 选取符合纳入标准的腹膜透析置管术后患者80例, 随机分为对照组和干预组, 各40例。对照组采用常规情志护理方法, 干预组在常规情志护理的基础上采用五行音乐联合耳穴贴压。干预2周后, 比较2组患者焦虑、抑郁情绪及睡眠质量。结果 干预2周后, 2组焦虑自评量表(SAS)和抑郁自评量表(SDS)评分均较干预前下降, 且干预组SAS、SDS评分低于对照组, 差异有统计学意义(P<0. 01)。干预后2组匹兹堡睡眠量表(PSQI)评分较干预前下降, 且干预组PSQI评分低于对照组, 差异有统计学意义(P<0. 01)。结论 常规情志护理的基础上, 采用五行音乐联合耳穴贴压能更好的改善腹膜透析患者焦虑、抑郁情绪, 提高患者睡眠质量。)